I am really stuck on this one.

3x – 5y = 9

y = 3x + 3

Printable View

- April 8th 2007, 11:35 AMPatienceSolve the system by substitution
I am really stuck on this one.

3x – 5y = 9

y = 3x + 3 - April 8th 2007, 11:39 AMJhevon
3x – 5y = 9 ........................(1)

y = 3x + 3 .....................(2)

from (2) we see y = 3x + 3,**substitute**3x + 3 for y in (1), we get:

3x – 5y = 9

=> 3x - 5(3x + 3) = 9

=>3x - 15x - 15 = 9

=> -12x = 24

=> x = -2

but y = 3x + 3

=> y = 3(-2) + 3

=> y = -3

so x = -2, y = -3